Efektivitas Senam Jantung Sehat terhadap Tekanan Darah dan Kualitas Tidur pada Lansia dengan Hipertensi - Istianah; Ni Putu Sari Indriani; Hapipah (LPPM STIKES Guna Bangsa, 2022)
Hypertension is a state of increased contraction of the arteries and increased blood pressure against the walls of blood vessels. One of the non-pharmacological therapies that can affect heart rate, blood pressure, relaxation, and sleep quality is healthy heart exercise. This study aims to determine the effect of healthy heart exercise on blood pressure and sleep quality in the elderly with hypertension. The research design used a pre-experimental design with One Group Pretest Posttest. The sample amounted to 16 respondents who were selected by purposive sampling by the inclusion criteria. The instruments used were sphygmomanometer and Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data were analyzed using Univariate and Bivariate. The results of data analysis using the Paired Sample t-Test showed a significance value of 0.000 (p-value <0.05), which means that there is an effect of healthy heart exercise on reducing blood pressure and improving sleep quality in hypertensive elderly. Based on the results of this study, it is expected that healthy heart gymnastics can be applied both to first-level health services and can be carried out at home regularly for the elderly who are affected by hypertension.